Answer:
see explanation
Step-by-step explanation:
let ∠BCE = x then ∠ECD = 5x - 6 and
∠BCE + ∠ECD = ∠BCD, substitute values
x + 5x - 6 = 162, that is
6x - 6 = 162 ( add 6 to both sides )
6x = 168 ( divide both sides by 6 )
x = 28
Hence
∠BCE = x = 28°
∠ECD = 5x - 6 = (5 × 28) - 6 = 140 - 6 = 134°
Answer:
The answer is A,C, and D
Step-by-step explanation:
The answer is below what the dude said
Answer: f(-3) = -27 & f(3) = 27
Step-by-step explanation:
(-3)^3
-27
(3)^3
27
-5x +3 =18
Subtract 3 from each side
-5x= 15
Divide by -5
x= -3